The method of Imam Al-Bayhaqi in narrators’ difference in his book Al-Sunan Al-Kabeer - Alsulami, Hammad Mahdi (Journal of Islamic Sciences, 2019)
Imam Al-Bayhaqi is one of the scientists of the critics who served the Prophet’s Sunnah through his many compositions and works. The hadeeth ingenuity has appeared in many of his works, including the book of Al-Sunan al-Kabeer, in which he mentioned many differences of narrators in hadeeths. The display of difference between narrators is one of the most important methods used by scientists and critics to refer to the illusions of narrators and the trouble of hadeeths. The method of Imam Al-Bayhaqi differed in his book Al-Sunan Al-Kabeer from one hadeeth to another and from one difference to another, and because his book is one of the sunnah books of the comprehensive of Fiqh and Hadeeth, It was necessary to know his method in that. The researcher followed the method inductive deductive approach, which in turn led to a number of results, the most important of which: -Imam Al-Bayhaqi of the scientists critics who have special provisions in hadeeths, and his book Al-Sunan al-Kabeer contains the hadeeth ingenuity and the critical approach Proof of this: -The difference between the narrators of what is influential in the hadeeth, and from what is not influential. -The purposes differed of Al-Bayhaqi to the difference between the narrators, some of which is explicit and clear in the Influential in of the hadeeth, including what is otherwise.